Do external commercial borrowings and financial development affect exports? - Ashis Kumar Pradhan; Gourishankar S. Hiremath (Cogent Business & Management, 2020)
In this study, we examine the competitiveness effect of currency depreciation in the presence of external commercial borrowing (ECBs) and low financial development. The estimates of autoregressive distributed lag (ARDL) show the contractionary effects of exchange rate depreciation on exports owing to increased liability denominated in foreign currency such as ECBs. We also find a positive relationship between bank credit and exports, but the marginal benefits of domestic credit diminish when the exchange rate depreciates. The findings of the study suggest that natural hedging does not act as a cushion against shocks and thus calls for the mandatory use of derivatives by firms. The development of domestic credit markets is essential to reap the benefits of currency depriciation in the export sector.
Keywords: F31; F34; G00; G23; 650; external commercial borrowing; financial development; currency depreciation; competitiveness effect; credit constraints; ARDL cointegration